Marketing of information products and services in public libraries in South West, Nigeria (2018)
The study examines the marketing of information products and services in public libraries in South West, Nigeria. A descriptive survey research design was adopted. The population comprises professionals and library officers. Questionnaire was used as means of data collection. The sections consist of A and B. Section A dwells on the socio-economic variables of the respondent, Section B consist on availability of information products and services as well as marketing and promotional strategies adopted by the libraries. One hundred and thirty copies of questionnaires were administered and data analysed. The study reveals that the public libraries in South West market their information products and services and also shows that lending of materials, user education, school services, referral services are highly available. Quick and long queries, adult literacy programmes, reading list and bibliographies, indexing and abstracting among others were available whereas translation services, rental of premises and CD-ROM services are not available. Findings on promotional strategies for marketing information products and services reveals that majority agreed with display and exhibition as well as creation of conducive environment as the type of promotional strategies adopted in the public library boards studied. On the marketing management strategies adopted, the study reveals that respect to users along with paying attention to users rated highest as the commonest marketing practice among the studied public library boards. Based on the findings, it is concluded that marketing of information products and services by the libraries has a lot to do towards entrenching marketing principles and practices.